Assessing the Impacts of Learning Capacity on Employee and Customer Satisfaction - H Salehi (Tehran University of Medical Sciences, 2005)
This paper examines the relationship of learning organization variables with job satisfaction, organizational commitment and customer satisfaction among employees of health insurance organizations in the context of Iran. This study was conducted in three health insurance organizations. Two hundred sixty five employees and 1220 customers were randomly and proportionally selected, with a response rate of 80% for employees and 70 % for customers. The Job Satisfaction and organizational commitment instrument used all Items of G.H.Shwepker [2001] questionnaires for JS&OC (job satisfaction and organizational commitment) .The dimensions of learning organization questionnaire (DLOQ) of Watkins and Marsik [1997,2001,2003] was used to measure the state of development of three health insurance organizations in terms of learning organization dimensions. A third questionnaire was used with an eleven elements (developed by the researcher) to assess customer satisfaction. In terms of reliability analysis for all the three questionnaires, a Test-R-Test was used to test external reliability and Alpha Cronbach for internal consistency. In addition to content and face validity, construct validity was confirmed through confirmatory factor analysis, correlation statistics, and inferential statistics ANOVA (Kruskal Wallis Test) and t-test, were used to asses the relationships among the factors. Job satisfaction was found to be moderately and positively correlated to organizational commitment and positively and moderately to learning organization dimensions. Organizational commitment is positively and weekly correlated to learning organization dimensions. The result of Kruskal Wallis Test shows that the organization with higher mean ranks scores in most of it's Learning organizations factors has higher result and significantly different result in terms of customer satisfaction in all CS (customer satisfaction) scales and subscales.